2005
DOI: 10.1093/pcp/pci073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Function of the Photoreceptors Phytochrome B and Phytochrome D in Nicotiana plumbaginifolia and Arabidopsis thaliana

Abstract: To investigate the mechanism of phytochrome action in vivo, NtPHYB, AtPHYB and phyD:green fluorescent protein (GFP) were overexpressed in Nicotiana plumbaginifolia and Arabidopsis thaliana. The expression of 35S:NtPHYB:GFP and 35S:AtPHYB:GFP complemented the tobacco hgl2 and Arabidopsis phyB-9 mutations, whereas the 35S:AtPHYD:GFP only rescued the hgl2 mutant. All three fusion proteins are transported into the nucleus in all genetic backgrounds. These data indicate that AtPHYD:GFP is biologically active and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…species, natural accessions or ecotypes) which may have been exposed to different selective pressures will likely evolve specific phytochrome‐dependent mechanisms to respond to light, even though the responses are initiated by the same Pr and Pfr biochemistry (Dudley and Schmitt ; Botto and Smith ; Chitwood et al ). Consistent to this notion, Fernandez et al () reported the functional divergence between Arabidopsis and N. tabacum PHYB‐clade of apoproteins found at the protein level in the control of hypocotyl elongation in N. plumbaginifolia . These authors used cross‐species complementation tests, and showed that while NtPHYB:GFP and AtPHYB:GFP could recover the hypocotyl phenotype of both AtphyB ( phyB‐9) and NpphyB ( hlg ) loss‐of‐function, AtPHYD:GFP could only rescue NpphyB , and not AtphyB , loss‐of‐function.…”
Section: Discussionmentioning
confidence: 72%
“…species, natural accessions or ecotypes) which may have been exposed to different selective pressures will likely evolve specific phytochrome‐dependent mechanisms to respond to light, even though the responses are initiated by the same Pr and Pfr biochemistry (Dudley and Schmitt ; Botto and Smith ; Chitwood et al ). Consistent to this notion, Fernandez et al () reported the functional divergence between Arabidopsis and N. tabacum PHYB‐clade of apoproteins found at the protein level in the control of hypocotyl elongation in N. plumbaginifolia . These authors used cross‐species complementation tests, and showed that while NtPHYB:GFP and AtPHYB:GFP could recover the hypocotyl phenotype of both AtphyB ( phyB‐9) and NpphyB ( hlg ) loss‐of‐function, AtPHYD:GFP could only rescue NpphyB , and not AtphyB , loss‐of‐function.…”
Section: Discussionmentioning
confidence: 72%
“…Recent work by Dong et al [ 35 ] demonstrated that different tobacco genotypes differ in the depth of photo-dependent dormancy and that the over-expression of NtPHYB1 prevents the induction of photo-dependent dormancy during seed maturation. Nicotiana species are known to have one PHYA gene and, due to duplications during Solanaceae genome evolution, several PHYB genes [ 35 , 36 , 37 , 38 , 39 ]. These light-sensing proteins regulate seed germination independently from each other, both spatially and temporally [ 17 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis is the sole plant species for which the full set of photoreceptor genes has been characterized (Demarsy and Fankhauser 2009;Inoue et al 2010;Nagatani 2010;Chaves et al 2011). In Solanaceae, photoperception and light signaling have been mainly investigated in tomato, tobacco and potato (Perrotta et al 2000;Weller et al 2001;Fernández et al 2005;Rutitzky et al 2009). High-throughput transcriptomic analyses have demonstrated extensive sequence and functional conservation among phenotypically distinct Solanaceae species potato, tomato, pepper, petunia, tobacco and Nicotiana benthamiana, although species-specific transcripts were also indentified (Rensink et al 2005;Rutitzky et al 2009).…”
Section: Discussionmentioning
confidence: 99%